The Effects of the Welding Parameters on Tensile Properties of RSW Junctions of DP1000 Sheet Steel - Elitas, M.; Demir, B. (Engineering, Technology & Applied Science Research, 2018)
In this study, the maximum tensile shear load bearing capacity of the resistance spot welded DP1000 steel was measured and the tensile shear properties of the joints were evaluated. The effects of different welding parameters on microstructure, microhardness and tensile shear properties were investigated. Weld processes were performed by using 5kA and 7kA weld currents and 2-6bar electrode pressures. The microstructure of the welded materials was evaluated and the hardness profiles were determined. Experimental results showed that increasing electrode pressure and weld current increased the tensile shear load bearing capacity. It was also observed that the expulsion had a negative effect on the tensile shear load bearing capacity.